2021
DOI: 10.1016/j.tranon.2020.100877
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of clinically actionable mutations in breast cancer ‘A cohort study’

Abstract: Breast cancer (BC) is a heterogeneous disease. Numerous chemotherapeutic agents are available for early stage or advanced/metastatic breast cancer to provide maximum benefit with minimum side effects. However, the clinical outcome of patients with the same clinical and pathological characteristics and treated with similar treatments may show major differences and a vast majority of patients still develop treatment resistance and eventually succumb to disease. It remains an unmet need to identify specific molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For example, it has been shown that BC's responses to therapeutic regimens vary due to the diverse genetic profiles among BC cells. 57 In addition, the presence of amino acids, carbohydrates, proteins, and metabolites in different culture media affects the aggregation of NPs and their consequent uptake, toxicity, and bioactivities in cells. 58 Some of these factors can be compared with those of other rare-earth nanostructures (e.g., Gd 2 O 3 , CeO 2 -Gd, and La 2 O 3 ) that are cytotoxic against glioblastoma and hepatoma cell lines.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…For example, it has been shown that BC's responses to therapeutic regimens vary due to the diverse genetic profiles among BC cells. 57 In addition, the presence of amino acids, carbohydrates, proteins, and metabolites in different culture media affects the aggregation of NPs and their consequent uptake, toxicity, and bioactivities in cells. 58 Some of these factors can be compared with those of other rare-earth nanostructures (e.g., Gd 2 O 3 , CeO 2 -Gd, and La 2 O 3 ) that are cytotoxic against glioblastoma and hepatoma cell lines.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…In this context, the study of the NK-tumor cell interaction has to consider the dynamic conditions that accompany tumor growth and its vascularization [ 195 , 196 , 197 , 198 ]. It is evident that, within a tumor mass, a strong heterogeneity is present due to the differential expression of altered genes (mutations, up and down regulation of genes, chromosomal/copy number alterations) in different cell populations, and the heterogeneity of the metabolic state of these cells [ 199 , 200 , 201 , 202 , 203 ]. The expression of mutated genes can be dependent on the metabolic state and the primary source of energy used by tumor cells, and vice versa, some mutations trigger metabolic responses [ 204 , 205 , 206 , 207 ].…”
Section: Tumor Cell Organoids: a More Reliable 3d Model To Study Tumor Cell Biology And Tumor-nk Cells Interactions?mentioning
confidence: 99%
“…Molecular markers, like BRCA1 or BRCA2 (breast cancer gene 1 or 2) germline mutations, are indicators of possible basal-like breast cancer development and are used to determine potential risk and guide treatment 6 . Recent large-scale sequencing efforts have led to the identification of the genes with the highest mutation rates in breast cancer, including TP53 , PIK3CA , AKT1 , PTEN , ERBB2 , ATM , CDH1 , APC , KRAS, NRAS 7 . Ongoing research will determine whether these mutations are “actionable” in order to lay the foundation for personalized medicine approaches.…”
Section: Introductionmentioning
confidence: 99%